2016
DOI: 10.1111/pme.12865
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Ketamine for Rapid Opioid Dose Reduction, Reversal of Opioid-Induced Neurotoxicity, and Pain Control in Terminal Care: Case Report and Literature Review

Abstract: OIN should be considered as an etiology of CNS dysfunction occurring with prolonged, high-dose opioid therapy. This case highlights the opioid-sparing and analgesic properties of low-dose ketamine, allowing reversal of OIN in the home hospice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Adverse effects were limited and acceptable by using a combination of ketamine and midazolam at low doses, which were reduced only in minority of cases. Safety data confirm previous observations (11).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Adverse effects were limited and acceptable by using a combination of ketamine and midazolam at low doses, which were reduced only in minority of cases. Safety data confirm previous observations (11).…”
Section: Discussionsupporting
confidence: 89%
“…While most observational studies suggested that ketamine may be helpful in different clinical conditions, either decreasing pain intensity or opioid doses (10), in a recent well powered placebo-controlled study no advantages were found with the use ketamine that was also associated to toxicity (7). Similar findings were found in a smaller study, although 50% of patients seemed to have had major analgesic responses and no major adverse effects were reported (11). These findings contrast the benefits from ketamine observed in many open-label series (10,(12)(13)(14)(15)(16)(17)(18)(19)(20) even for prolonged periods of time (21,22).…”
Section: Discussionmentioning
confidence: 65%
“…10 Although developed as an anesthetic, ketamine at subanesthetic doses can reverse pain crises in patients taking opioid medications 11 and also reverses opioid-induced neurotoxicity. 12 Through multiple routes, with and without other adjuvant pain medications, ketamine's varied actions have been exploited to optimize cancer pain control.…”
Section: The Who Analgesic Ladder: Critiquementioning
confidence: 99%
“…Subanesthetic doses are more commonly associated with mild and transient impairments in attention, memory, and judgment (Quibell, Prommer, Mihalyo, Twycross, & Wilcock, 2011;Winegarden, Carr, & Bradshaw, 2015). If they occur, these effects can generally be controlled by concurrent administration of low doses of benzodiazepine or haloperidol, such as lorazepam 0.5 to 1 mg.…”
Section: Possible Side Effectsmentioning
confidence: 99%
“…However, given the small number of patients and the clinical heterogeneity in these studies, the evidence was insufficient to assess the benefits and harms of ketamine for the treatment of cancer pain (Afsharimani, Kindl, Good, & Hardy, 2015). Most of the evidence supporting ketamine's efficacy as an analgesic for cancer pain is from case reports, retrospective surveys, or uncontrolled studies in patients with refractory neuropathic, bone, and mucositis-related pain (Quibell et al, 2011;Winegarden et al, 2015).…”
Section: Use In Pain Management and Palliative Carementioning
confidence: 99%